O09.5 Prep awareness, eligibility, and acceptability among heterosexuals recruited from community-based hiv testing sites. (8th July 2017) - Roth, Alexis M; Felsher, Marisa A; Martinez-Donate, Ana; Krakower, Douglas; Szep, Zsofia
Abstract : Introduction: Studies demonstrate pre-exposure prophylaxis (PrEP) can decrease HIV transmission among heterosexual men and women. To inform targeted promotional campaigns, it is necessary to identify those most likely to benefit from this intervention and assess their knowledge and attitudes towards PrEP. Methods: We recruited individuals>18 years old from 4 community-based rapid HIV counselling and testing sites in Philadelphia. They completed a brief survey and screener for PrEP eligibility. Eligibility was based on reporting "yes" to: sex with a partner of unknown or HIV positive status, sex in exchange for drugs/money, recent sexually transmitted infection, or syringe sharing. Chi-squared tests were used to examine factors associated with eligibility, knowledge, and attitudes among 111 self-identified heterosexuals. Results: The sample is 61% male, with race/ethnicity of Black (48%), Latino (40%), White (9%) and other (3%), and median age 44. 31% screened PrEP eligible. Among males and females, eligibility was associated with reporting sex exchange, sex with persons of unknown HIV status, and recent STI (all p<0.05). By race/ethnicity, only syringe sharing differs significantly: 41.7% of Latinos, 42.9% of White participants and no Black or Other participants (p<0.04) reported sharing. Only 24% of participants had heard of PrEP; knowledge did not vary by group. A sizable minority reported concerns about side effects (44%) and talking to a doctor about PrEP (30%). However, 23% were extremely likely or somewhat likely (30%) to use PrEP to prevent HIV in the future. Conclusion: We identified a diverse and at-risk heterosexual population within community-based HIV counselling and testing. Most participants were unaware of PrEP, signifying promotional information is not reaching this population. Having rapid HIV testers screen for PrEP eligibility and educate clients about PrEP may be an effective way to increase PrEP awareness and acceptability among heterosexuals.